2016
DOI: 10.3892/mmr.2016.5482
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urinary bladder fibrogenesis in a mouse model of long-term ketamine injection

Abstract: Long-term ketamine abuse has been shown to affect the lower urinary tract and result in interstitial cystitis-like syndrome. However, the causative mechanism of ketamine-induced dysfunction remains unclear. The present study aimed to investigate the physiological, histological and molecular changes on ketamine-associated cystitis (KC) in a mouse model. Both male and female Balb/c mice were separately distributed into the control group (normal saline) and ketamine group, which received ketamine hydrochloride (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Therefore, it may be assumed that these differences are also present between rodents and humans. In a similar study, it was revealed that 25 mg/kg of ketamine induced rat bladder inflammation and cyclooxygenase-2 expression (50), whereas 100 mg/kg of ketamine did not cause significant inflammation in mouse bladder tissues (51). In the present study, we provide additional evidence that the gene regulation of CBS, ADORA1 and WIF1 was different between mouse bladder tissues and human urothelial cells.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it may be assumed that these differences are also present between rodents and humans. In a similar study, it was revealed that 25 mg/kg of ketamine induced rat bladder inflammation and cyclooxygenase-2 expression (50), whereas 100 mg/kg of ketamine did not cause significant inflammation in mouse bladder tissues (51). In the present study, we provide additional evidence that the gene regulation of CBS, ADORA1 and WIF1 was different between mouse bladder tissues and human urothelial cells.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous animal studies have demontrated that long-term ketamine treatment can lead to bladder fibrosis, which is an important cause of bladder abnormalities, including decreased capacity, lower compliance and impaired detrusor function ( 41 , 42 ). Song et al ( 41 ) demonstrated that the inflammatory mediators in KIC increased the expression of collagen type-I (COL-I) and α-SMA, which leads to thickening of the bladder basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al ( 41 ) demonstrated that the inflammatory mediators in KIC increased the expression of collagen type-I (COL-I) and α-SMA, which leads to thickening of the bladder basement membrane. Furthermore, Shen et al ( 42 ) conducted whole genome analysis and reported that the expression of fibrotic genes, including fibronectin, TGF-β1 and COL-I, were upregulated in bladder tissues with KIC. This enriched expression was considered to be a sensitive marker of active fibrosis development.…”
Section: Discussionmentioning
confidence: 99%
“…Two micrograms of RNA were reverse‐transcribed to complementary DNA, using the ThermoScript reverse transcription polymerase chain reaction (RT‐PCR) System (Invitrogen, Grand Island, NY). The expression of fibrosis markers including collagen type 1, 10 collagen type 3, 10 transforming growth factor‐β 1 (TGF‐β1), and fibroblast growth factor 2 (FGF 2), 11 and ischemia markers including hypoxia‐inducible factor‐1 α (HIF‐1α) 12 and vascular endothelial growth factor A (VEGF A) 12 was quantified using CFX Maestro Real‐Time PCR Instruments (BIO‐RAD Laboratories, Inc, Hercules, CA) in a 25‐µL volume, using SYBRGreen PCR Master Mix (QIAGEN, Valencia, CA). Relative gene expression was normalized with the expression of β‐actin.…”
Section: Methodsmentioning
confidence: 99%